Thermal radiation and chemical reaction effects on unsteady magnetohydrodynamic third grade fluid flow between stationary and oscillating plates - Idowu, Amos Sesan; Sani, Usman (Zielona Góra: Uniwersytet Zielonogórski)
An analysis was carried out for an unsteady magnetohydrodynamic(MHD) flow of a generalized third grade fluid between two parallel plates. The fluid flow is a result of the plate oscillating, moving and pressure gradient. Three flow problems were investigated, namely: Couette, Poiseuille and Couette-Poiseuille flows and a number of nonlinear partial differential equations were obtained which were solved using the He-Laplace method.
Keywords: third grade fluid; plane Couette; Poiseuille and Couette-Poiseuille flow; magnetohydrodynamics flow; stationary plate; oscillating plate; thermal radiation; chemical reaction